Pedagogical Practices Within The Competency: Baset Pproach amony Primary School Teachers of Arabic in Mostaganem Province - بن عروم فاطمة; قيدوم أحمد (International Journal of Social Communication, 2025)
The study aimed to explore the pedagogical practice under the Competency-Based Approach (CBA) among primary school teachers specializing in the Arabic language, and to examine differences in pedagogical practice related to professional experience, field of study, and the institution where Arabic language teachers were trained within the education sector in Mostaganem province. The study sample consisted of 400 male and female primary school teachers. A tool was used to measure pedagogical practice, and the descriptive method was adopted. After verifying the psychometric properties of the tool, the study reached the following results: There are no differences in the level of pedagogical practice attributable to the institution where the Arabic language primary teacher was trained. There are no differences related to professional experience. There are no differences between the scientific and literary educational tracks in their pedagogical practice under the Competency-Based Approach.